Using Google Earth for Internet GIS - Henry, Andrew (2009)
The goal of this research is to investigate the potential of using Google Earth for Internet GIS applications. The study specifically examines the use of vector and attribute data and the potential of displaying and processing this data in new ways using the Google Earth platform. It has increasingly been recognised that future developments in GIS will centre on Internet GIS, and in three major areas: GIS data access, spatial information dissemination and GIS modelling/processing. Google Earth is a 3-D geobrowser that has been termed the ‘the democratisation of GIS’ and is one of a family of geobrowsers that offer a free and easy to use service that enable data with a spatial component to be overlain on top of a 3-D model of the Earth. This research creates a methodological framework to achieve its goal that consists of three major parts: a database tier, an application tier and a client tier. As proof of concept a web prototype has been developed, called VISQUE – VISualise and Query Using Earth, which integrates a diverse range of datasets from 18th century Iceland and lets users direst queries and create visualisations of this custom data. The results revealed that both vector and attribute data can be effectively represented and visualised using Google Earth. Moreover, the functionality to query custom data and visualise results has been added to the Google Earth platform.